Directory of women physicians in the U.S.
Alphabetical and geographical listings of American physicians in the United States and elsewhere. Also includes osteopathic physicians, affiliates, and medical students who belong to the American Medical Association. Coded biographical data (name, address, birth, medical school, licensing, specialty, type of practice, and certification) appear in geographical section. Includes list of medical schools throughout the world.